2018
DOI: 10.1001/jamacardio.2017.4771
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Medicare Expenditure Growth and Mortality Rates in Patients With Acute Myocardial Infarction

Abstract: Health improvements for patients with acute myocardial infarction varied across hospitals and were associated with the diffusion of cost-effective care, such as early percutaneous coronary intervention and, to a lesser extent, postacute care, rather than overall expenditure growth. Interventions designed to promote hospital adoption of cost-effective care could improve patient outcomes and, if accompanied by cuts in cost-ineffective care (inside and outside of the hospital setting), also reduce expenditures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…A trend of increase in ED visits was observed throughout the years, consistent with previous reports [20]. This disparity in the trends of ED utilization and the other resources could possibly be attributed to increased awareness and caution by the AMI survivors and their healthcare providers to complaints that could be related to an acute cardiac condition.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A trend of increase in ED visits was observed throughout the years, consistent with previous reports [20]. This disparity in the trends of ED utilization and the other resources could possibly be attributed to increased awareness and caution by the AMI survivors and their healthcare providers to complaints that could be related to an acute cardiac condition.…”
Section: Discussionsupporting
confidence: 88%
“…Importantly, our analysis includes all hospitalizations rather than those for a particular cause, while previous reports showed that about 30% of readmissions are for reasons unrelated to the original condition [19]. In partial consistency with our findings, a recent report from the US found significant differences across the country and between different Table 1 The baseline characteristics of the study population by study year (Continued ) Year 2003 2004 2005 2006 2007 2008 2009 2010 2011 2012 2013 2014 2015 p for trend n 426 1233 1822 2491 3111 3695 4211 4664 5067 5482 5650 5223 services, in ambulatory and outpatient resource utilization and expenditure following hospital discharge with an AMI (31-180 days) between 1999 and 2014 [20]. The current study was not designed to determine the causes for the observed time dependent changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study was not able to determine the time to reperfusion, as the hours and minutes of admission and treatments were not available. A study involving the US Medicare found that a decreased 180-day mortality was associated with an early PCI, which was defined as the PCI performed at the first day of the index hospitalization [28]. In our study, the median stay of 3 days for patients undergoing PCI during the first hospitalization indicated that most PCIs were performed without a lengthy delay.…”
Section: Strengths and Limitationsmentioning
confidence: 49%
“…AKI, acute kidney injury; IV, inverse variance; df, degrees of freedom. stent technology, a significantly larger number of patients are undergoing coronary catheterization (30). Concurrently, there is a growing need to limit post-procedural complications and enhance clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%